2015
DOI: 10.1016/j.cortex.2015.06.026
|View full text |Cite
|
Sign up to set email alerts
|

Differences in fMRI intersubject correlation while viewing unedited and edited videos of dance performance

Abstract: Intersubject correlation (ISC) analysis of functional magnetic resonance imaging (fMRI) data provides insight into how continuous streams of sensory stimulation are processed by groups of observers. Although edited movies are frequently used as stimuli in ISC studies, there has been little direct examination of the effect of edits on the resulting ISC maps. In this study we showed 16 observers two audiovisual movie versions of the same dance. In one experimental condition there was a continuous view from a sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
34
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 44 publications
2
34
0
Order By: Relevance
“…For example, one popular approach for one condition was to acquire a null distribution for the whole brain by randomizing the time series across voxels and time points (e.g., circularly shifting each subject’s time series by a random lag so that they were no longer aligned in time across the subjects) (Kauppi et al, 2010; Nummenmaa et al, 2012; Abrams et al, 2013; Kauppi et al, 2014; Pajula and Tohka, 2014; Trost et al, 2015; Herbec et al, 2015; Bridwell et al, 2015). For comparing two conditions, a different permutation test was used on the N elements { z ij , i < j } through element-wise sign flipping (Kauppi et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, one popular approach for one condition was to acquire a null distribution for the whole brain by randomizing the time series across voxels and time points (e.g., circularly shifting each subject’s time series by a random lag so that they were no longer aligned in time across the subjects) (Kauppi et al, 2010; Nummenmaa et al, 2012; Abrams et al, 2013; Kauppi et al, 2014; Pajula and Tohka, 2014; Trost et al, 2015; Herbec et al, 2015; Bridwell et al, 2015). For comparing two conditions, a different permutation test was used on the N elements { z ij , i < j } through element-wise sign flipping (Kauppi et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…One common practice in the literature is to obtain the group mean directly by averaging the ISC values across N subject pairs { r ij , i > j } (Kauppi et al, 2010; Nummenmaa et al, 2012; Honey et al, 2012; Pajula and Tohka, 2014; Kauppi et al, 2014; Bridwell et al, 2015; Lillywhite et al, 2015; Herbec et al, 2015). However, mathematically, the averaging as implemented in the ISC Toolbox (Kauppi et al, 2014) is problematic for the following reason.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In line with this, shuffling a movie using discontinuity edits markedly lowers ISC in higher‐order associative and frontal cortices across observers [Hasson et al, ; Lerner et al, ]. In contrast, adding continuity edits to depiction of continuous action actually increases ISC in the occipital, ventral temporal, and parietal cortices [Herbec et al, ] leaving ISCs in the posterior temporal regions unaffected. Indeed, we did not observe significant differences in the event‐related responses to scene onsets when the clips were preceded by the previous clip of the same movie (Consecutive condition) versus a clip from a different movie (Interleaved condition; Fig.…”
Section: Discussionmentioning
confidence: 98%
“…It is also relevant to note that the occurrence of camera devices at times also 21 corresponded to times with very little activity occurring within the scene, which in 22 some instances may have contributed to the decrease in activation. However, recent 23 results (Herbec et al, 2015) using unedited and edited videos of the same dance 24 performance revealed that editing activates a wide network of brain areas including 25 frontal cortex and possibly interactions within these brain networks might interact with 1 pSTS and FFA activity. 2 3 Differences between the groups of observers were apparent in the results of 4 the chi-squared analysis revealing a greater frequency of significantly activated 5 timeframes for novices viewing the prosocial CCTV footage only compared to CCTV 6 operators.…”
mentioning
confidence: 99%